Reproductive potential of state: three levels of macro regulation (Journal of Economic Research & Business Administration, 2015)
Article is devoted to identifi cation of interrelation of the state and competitive sectors of economy in the conditions of the being formed market. Need of ranging of the system relations locates in article. It allows to establish hierarchy at the level of quantitative parameters, at institutional and operational levels. This analysis shows that quantitative parameters of industrial potential are under construction on system of the public expenditures. Institutional communication is based on system of government procurements. From the applied point of view effective reproduction in this aspect is based on institutes and functions of state-private partnership.
Keywords: public sector; competitive sector; public expenditures